Increasing the maturity of measurements of essential climate variables (ECVs) at Italian atmospheric WMO/GAW observatories by implementing automated data elaboration chains. (April 2020) - Naitza, Luca; Cristofanelli, Paolo; Marinoni, Angela; Calzolari, Francescopiero; Roccato, Fabrizio; Busetto, Maurizio; Sferlazzo, Damiano; Aruffo, Eleonora; Di Carlo, Piero; Bencardino, Mariantonia; D'Amore, Francesco; Sprovieri, Francesca; et al.
Abstract: In the framework of the National Project of Interest NextData, we developed automatic procedures for the flagging and formatting of trace gases, atmospheric aerosols and meteorological data to be submitted to the World Data Centers (WDCs) of the Global Atmosphere Watch program of the World Meteorological Organization (WMO/GAW). In particular, the atmospheric Essential Climate Variables (ECVs) covered in this work are observations of near-surface trace gas concentrations, aerosol properties and meteorological variables, which are under the umbrella of the World Data Center for Greenhouse Gases (WDCGG), the World Data Center for Reactive Gases, and the World Data Center for Aerosol (WDCRG and WDCA). We developed an overarching processing chain to create a number of data products (data files and reports) starting from the raw data, finally contributing to increase the maturity of these measurements. To this aim, we implemented specific routines for data filtering, flagging, format harmonization, and creation of data products, useful for detecting instrumental problems, particular atmospheric events and quick data dissemination towards stakeholders or citizens. Currently, the automatic data processing is active for a subset of ECVs at 5 measurement sites in Italy. The system represents a valuable tool to facilitate data originators towards a more efficient data production. Our effort is expected to accelerate the process of data submission to WMO/GAW or to other reference data centers or repositories. Moreover, the adoption of automatic procedures for data flagging and data correction allows to keep track of the process that led to the final validated data, and makes data evaluation and revisions more efficient by improving the traceability of the data production process. Highlights: Increasing the maturity of measurements by automatic data processing. "R" scripts for the automatic processing of atmospheric ECVs. Automatic production of plots for data control and report. Common Data Model compliant with Global Atmosphere Watch. Developed "R" scripts are available in open access.